Restructuring of anterior cruciate ligament transplant according to mri data - Krasnoperov, Sergiy; Didenko, Inna; Titarchuk, Rostyslav; Gricenko, Aleksandra; Golovakha, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Anterior crucial ligament (ACL) injury is one of the most common injuries of the knee. Magnetically resonance imaging (MRI) is an important method to evaluate and identify the transplant complications associated with ACL reconstruction. Objective: to develop criteria for evaluating new criteria of ACL graft restructuring. Methods: 95 patients at 3, 6, 9 and 12 months after ACL restoration using MRI are studied. ACL remodeling evaluated by MRI-signal intensity in T2 and proton density-weighted sequences (PDW), as well as the degree of homogeneity, using tribal scale. To eliminate subjectivity analysis of MRI-pictures used ratio signal/noise ratio. Data compared to intact ACL in 50 patients is obtained. Results: values of the signal/noise ratio (SNR) decreases from 3 to 9 months after the surgery, indicating graft restructuring during this period in all its parts (femoral, tibial and median). There is no difference in ratio signal/noise coefficient obtained 9 and 12 months after the surgery. It is found that even after 12 months after the operation signal intensity of ACL transplantation does not reach intact ligament values. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusion:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> it is developed method of evaluating the dynamics of recovery after ACL graft using the analysis of MRI images. It involves determining signal strength using the signal/ noise ratio and qualitative evaluation of ACL graft with general view uniformity using tribal scale. It is developed criteria of MRI evaluation for intraarticular ACL graft restructuring. The results should be considered when planning a program of rehabilitation and development of methods aimed at the acceleration of biological graft remodeling after ACL reconstruction.